Shape memory pre-stressed anchor net material and preparation method thereof

By using nano-concave-convex rods and modified styrene-methyl acrylate-butadiene copolymer in the anchor mesh material, the problem of limited support effect of polyester anchor mesh under high ground stress is solved, and the high strength and shape memory prestressed support effect of anchor mesh is achieved.

CN119753869AActive Publication Date: 2025-04-04CCTEG COAL MINING RES INST +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411865431.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The support effect of polyester anchor mesh under high ground stress and strong mining is limited, making it difficult to achieve prestressed support, and the strength and stiffness are insufficient.

Method used

The shape memory prestressed anchor mesh material is used, and the preparation method includes treating the nano-concave and convex rods to form active sites of carbon-carbon double bonds on the surface, and combining with the modified styrene-methyl acrylate-butadiene copolymer to improve the crystallinity and orientation of the anchor mesh through stress-induced crystallization.

Benefits of technology

The tensile strength, Young's modulus and toughness of the anchor net are improved, and its shape memory prestressed support effect in broken tunnels is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753869A_ABST
    Figure CN119753869A_ABST
Patent Text Reader

Abstract

The invention provides a shape memory pre-stressed anchor net material and a preparation method thereof. The preparation method comprises the following steps: preparing a modified styrene-methyl acrylate-butadiene copolymer taking attapulgite as a chemical crosslinking point; the preparation method comprises the following steps: stirring and mixing 100-110 parts by mass of the modified styrene-methyl acrylate-butadiene copolymer, 3-7 parts by mass of a shape memory accelerator, 1-8 parts by mass of a shape memory critical temperature regulator, 1-2 parts by mass of an anti-aging agent, 5-7 parts by mass of a reinforcing agent, 1-3 parts by mass of a plasticizer, 1 part by mass of an antistatic agent and 1-2 parts by mass of a flame retardant, and melting at 100-150 DEG C; and spinning and weaving the melt to obtain the anchor net material. The preparation method has the characteristics of simple process, low cost and easiness in popularization and application. When the anchor net material provided by the invention is deformed under the action of external force, the nano attapulgite is a crystal nucleus, the crystallinity and orientation degree of an anchor net matrix are further improved by stress induced crystallization, and the supporting effect of the anchor net is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new anchor net materials, and in particular to a shape memory prestressed anchor net material and a preparation method thereof. Background Art

[0002] Anchor net support technology is one of the important means of controlling the surrounding rock of coal mine tunnels, and anchor net materials are the key core of anchor net support technology. Under high ground stress and strong mining action, the surrounding rock of coal mine tunnels has a large deformation. The principle of anchor net is to use anchor net support to strengthen and improve the shear resistance of rock strata within a certain range of the tunnel roof, form a reinforced pressure arch, resist the deformation of the tunnel surrounding rock, and achieve the purpose of supporting and maintaining the tunnel. Its specific function is to anchor the anchor net under a certain preload force, so that the composite rock strata within the end anchor range form a composite beam under the elastic compression of the anchor net, and at the same time, use the anchor cable anchored in the stable rock stratum to suspend the composite beam under a certain preload force, so as to further enhance the support strength of the composite beam. Compared with metal mesh, polyester anchor net has the advantages of flexibility, lightness, strong acid and alkali corrosion resistance, and fast access speed. However, the strength and stiffness of polyester anchor net still need to be improved compared with metal mesh. At the same time, the stiffness of polyester anchor net is weak, and it is difficult to achieve prestressed support, and the support effect is limited.

[0003] Therefore, it is urgent to develop new shape memory prestressed anchor mesh materials and preparation methods suitable for coal mines and broken tunnels and promote their application. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. The present application proposes a shape memory prestressed anchor mesh material and a preparation method thereof, the preparation method having the characteristics of simple process, low cost and easy promotion and application. When the anchor mesh material provided by the present application is deformed by external force, the nano-convexo-rods are the crystal nuclei, and the stress-induced crystallization will further improve the crystallinity and orientation of the anchor mesh matrix, thereby improving the support effect of the anchor mesh.

[0005] According to an embodiment of the first aspect of the present application, a method for preparing a shape memory prestressed anchor mesh material is provided, comprising the following steps:

[0006] The nano-attapulgite is treated to form active sites of carbon-carbon double bonds on its surface; the modified nano-attapulgite is added to a mixed active monomer, and reacted at 250-300° C. for 120-130 minutes under the action of a composite catalyst and a protective atmosphere to obtain a modified styrene-methyl acrylate-butadiene copolymer with the attapulgite as a chemical crosslinking point;

[0007] In parts by mass, 100-110 parts of the modified styrene-methyl acrylate-butadiene copolymer, 3-7 parts of a shape memory accelerator, 1-8 parts of a shape memory critical temperature regulator, 1-2 parts of an anti-aging agent, 5-7 parts of a reinforcing agent, 1-3 parts of a plasticizer, 1 part of an antistatic agent and 1-2 parts of a flame retardant are stirred and mixed and melted at 100-150° C. The melt is spun and woven to obtain an anchor net material.

[0008] In some embodiments, the method for treating the nano-convex rod to form active sites of carbon-carbon double bonds on its surface is: treating the nano-convex rod with (3-propyleneoxypropyl)tris(trimethylsiloxy)-silane, 3(trimethoxysilyl)butyl methacrylate and 3-(trimethylsiloxy)propylene in a mass ratio of 4:1:1.

[0009] In some embodiments, the mixed reactive monomers include styrene, methyl methacrylate, and butadiene in a mass ratio of 2:1:5.

[0010] In some embodiments, the composite catalyst includes hexachloroplatinic (IV) acid and ferric nitrate in a mass ratio of 1:7.

[0011] In some embodiments, the shape memory promoter includes vinyl polysilsesquioxane and amino polysilsesquioxane in a mass ratio of 5:1.

[0012] In some embodiments, the shape memory critical temperature regulator includes polylactic acid, polycaprolactone and polyglycolide in a mass ratio of 1:1:3.

[0013] In some embodiments, the anti-aging agent includes ethyl 5-bromoindole-2-carboxylate and 4-bromo-2-trifluoromethylquinoline in a mass ratio of 1:2.

[0014] In some embodiments, the enhancer includes pentaerythritol glycidyl ether, ethylene glycol diglycidyl ether, and bisphenol A diglycidyl ether in a mass ratio of 4:1:1.

[0015] According to an embodiment of the second aspect of the present application, a shape memory prestressed anchor mesh material is provided, which is obtained by the preparation method described in any of the above embodiments.

[0016] According to an embodiment of the third aspect of the present application, it is proposed that the anchor mesh material described in any of the above embodiments be used in shape memory prestressed support for broken tunnels.

[0017] The anchor net material of the present application contains modified convexo-rods with a certain aspect ratio, which play the role of nanoparticle reinforcement. When the anchor net receives an external load, the nano-convexo-rods can act as stress concentration points, induce a large number of silver streaks and shear bands, absorb energy to prevent the anchor net from being damaged, and at the same time, the nano-convexo-rods can organize the silver streaks to develop into cracks as fixed points, thereby improving the strength of the anchor net. In addition, the styrene segment in the modified styrene-methyl acrylate-butadiene copolymer, the side benzene ring in the butadiene segment, and the carbon-carbon double bond form a π-π conjugation phenomenon, which enhances the interaction between the molecular chains inside the anchor net, and improves the tensile strength and Young's modulus of the anchor net; at the same time, the side methyl and ester groups of the methyl methacrylate segment in the modified styrene-methyl acrylate-butadiene copolymer are symmetrically distributed along the main chain, the internal rotation barrier is small, and the molecular chain flexibility is good, thereby improving the toughness and impact resistance of the anchor net. Finally, the modified styrene-methyl acrylate-butadiene copolymer is a reversible phase, the chemical cross-linking point attapulgite of the modified styrene-methyl acrylate-butadiene copolymer is a fixed phase, and the anchor mesh material exhibits shape memory properties, which can realize prestressed anchor mesh support in tunnels.

[0018] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0020] Figure 1 It is a flow chart of the method for preparing anchor net material proposed in one embodiment of the present application. DETAILED DESCRIPTION

[0021] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the present application includes all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.

[0022] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0023] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0024] To achieve the above-mentioned purpose, according to the embodiment of the first aspect of the present application, a method for preparing a shape memory prestressed anchor mesh material is proposed. Figure 1 As shown, the following steps are included:

[0025] S1: treating the nano-attapulgite to form active sites of carbon-carbon double bonds on its surface; adding the modified nano-attapulgite to the mixed active monomers, reacting at 250-300° C. for 120-130 min under the action of a composite catalyst and a protective atmosphere to obtain a modified styrene-methyl acrylate-butadiene copolymer with the attapulgite as a chemical crosslinking point;

[0026] S2: In parts by mass, 100-110 parts of modified styrene-methyl acrylate-butadiene copolymer, 3-7 parts of shape memory accelerator, 1-8 parts of shape memory critical temperature regulator, 1-2 parts of anti-aging agent, 5-7 parts of reinforcing agent, 1-3 parts of plasticizer, 1 part of antistatic agent and 1-2 parts of flame retardant are stirred and mixed and melted at 100-150°C, and the melt is spun and woven to obtain an anchor mesh material.

[0027] Among them, in S1, the nano-concave convex rods are activated and treated by (3-propyleneoxypropyl) tris(trimethylsiloxy)-silane, methacrylate-3(trimethoxysilyl)butyl ester and 3-(trimethylsiloxy)propylene in a mass ratio of 4:1:1, and carbon-carbon double bond active sites are introduced on the surface of the nano-concave convex rods through amphiphilic substances; even if the active sites of carbon-carbon double bonds are formed on the surface of the nano-concave convex rods, the modified nano-concave convex rods are added to a mixed active monomer composed of styrene, methyl methacrylate and butadiene, wherein the mass ratio of styrene, methyl methacrylate and butadiene is 2:1:5; then a composite catalyst composed of hexachloroplatinic (IV) acid and ferric nitrate in a mass ratio of 1:7 is added, auxiliary heating is performed to promote the polymerization reaction of carbon-carbon double bonds, and a protective gas such as nitrogen is introduced, and the reaction is carried out at 250-300°C in a microwave reaction tube for 120-130 minutes to prepare a modified styrene-methyl acrylate-butadiene copolymer with concave convex rods as chemical crosslinking points.

[0028] The present application utilizes (3-propyleneoxypropyl) tris(trimethylsiloxy)-silane, methacrylate-3(trimethoxysilyl)butyl ester and 3-(trimethylsiloxy)propylene in a mass ratio of 4:1:1 to jointly treat nano-concave convex rods, so that a large number of polar groups are formed on the surface of the nano-concave convex rods. The molecular repulsion between the polar groups makes the concave convex rods disperse more evenly and prevents them from agglomerating. In the process of forming the anchor net material, the chemical cross-linking point concave convex rods and modified styrene-methyl acrylate-butadiene copolymer inside the anchor net are dispersed more evenly, the overall performance is improved, and the support effect is improved. When the anchor net made by the anchor net material is deformed by external force, the nano-concave convex rods are the crystal nuclei, and the stress-induced crystallization will further improve the crystallinity and orientation of the anchor net matrix, thereby improving the support effect of the anchor net.

[0029] Among them, in S2, the set chemical amounts of modified styrene-methyl acrylate-butadiene copolymer, shape memory promoter, shape memory critical temperature regulator, anti-aging agent, reinforcing agent, plasticizer, antistatic agent and flame retardant are stirred and mixed by mass and melted at 100-150°C, and the melt is spun and woven to obtain the anchor mesh material.

[0030] In this embodiment, the anchor net material includes 100-110 parts by mass of modified styrene-methyl acrylate-butadiene copolymer. In some embodiments, the modified styrene-methyl acrylate-butadiene copolymer has a mass fraction of 100, 101, 104, 105, 107, 108 or 110 parts. If the modified styrene-methyl acrylate-butadiene copolymer has a small mass fraction, such as less than 100 parts, the molecular weight of the formed shape memory prestressed anchor net material is low and the tensile strength is not high. If the modified styrene-methyl acrylate-butadiene copolymer has a large mass fraction, such as greater than 110 parts, the shape recovery rate of the formed shape memory prestressed anchor net material is low and the shape memory performance is weak.

[0031] In this embodiment, the anchor mesh material includes 3-7 parts by weight of a shape memory promoter, wherein the shape memory promoter includes vinyl polysilsesquioxane and amino polysilsesquioxane in a mass ratio of 5:1. In some embodiments, the mass proportion of the shape memory promoter is 3 parts, 4 parts, 5 parts, 6 parts or 7 parts, etc. If the proportion of the shape memory promoter is small, such as less than 3 parts, the shape recovery rate and shape recovery rate of the formed shape memory prestressed anchor mesh material are low. If the proportion of the shape memory promoter is large, such as more than 7 parts, the tensile strength of the formed shape memory prestressed anchor mesh material is low and the mechanical properties are insufficient.

[0032] In this embodiment, the anchor mesh material includes 1-8 parts by weight of a shape memory critical temperature regulator, wherein the shape memory critical temperature regulator includes polylactic acid, polycaprolactone and polyglycolide in a mass ratio of 1:1:3. In some embodiments, the mass fraction of the shape memory critical temperature regulator is 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, etc. If the mass fraction of the shape memory critical temperature regulator is small, such as less than 1 part, the shape memory critical temperature of the formed shape memory prestressed anchor mesh material is high, and a higher temperature is required for shape recovery. If the mass fraction of the shape memory critical temperature regulator is large, such as greater than 8 parts, the mechanical properties of the formed shape memory prestressed anchor mesh material are lost, and the tensile strength is insufficient.

[0033] In this embodiment, the anchor mesh material includes 1-2 parts by weight of an anti-aging agent, wherein the anti-aging agent includes 5-bromoindole-2-carboxylic acid ethyl ester and 4-bromo-2-trifluoromethylquinoline in a mass ratio of 1:2. In some embodiments, the anti-aging agent has a mass fraction of 1 or 2 parts. If the anti-aging agent has a small mass fraction, such as less than 1 part, the formed shape memory prestressed anchor mesh material ages quickly and the mechanical properties decay quickly. If the anti-aging agent has a large mass fraction, such as more than 2 parts, the mechanical properties and shape memory properties of the formed shape memory prestressed anchor mesh material are affected.

[0034] In this embodiment, the anchor mesh material includes 5-7 parts by weight of a reinforcing agent, wherein the reinforcing agent includes pentaerythritol glycidyl ether, ethylene glycol diglycidyl ether and bisphenol A diglycidyl ether in a mass ratio of 4:1:1. In some embodiments, the mass fraction of the reinforcing agent is 5 parts, 6 parts or 7 parts, etc. If the mass fraction of the reinforcing agent is small, such as less than 5 parts, the reinforcing effect of the formed shape memory prestressed anchor mesh material is insufficient and the strength is lost. If the mass fraction of the reinforcing agent is large, such as greater than 7 parts, the rigidity of the shape memory prestressed anchor mesh material is high, but the flexibility is reduced.

[0035] In this embodiment, the anchor mesh material includes 1-3 parts by weight of plasticizer, wherein the plasticizer includes 3-aminophthalic acid dimethyl ester and 4-hydroxybenzoic acid 2-ethylhexyl ester. In some embodiments, the plasticizer has a weight of 1 part, 2 parts or 3 parts. If the weight of the plasticizer is larger, such as more than 3 parts, the mechanical properties of the shape memory prestressed anchor mesh material will be affected.

[0036] In this embodiment, the anchor net material includes 1 part by weight of an antistatic agent, wherein the antistatic agent includes (acryloylamidomethyl)cellulose acetate propionate (CAS No. 97635-64-8) and sodium carboxymethyl cellulose (CAS No. 404943-62-0). The antistatic agent is used to reduce static electricity accumulation and prevent static electricity accumulation, thereby protecting equipment and personnel safety.

[0037] In this embodiment, the anchor mesh material includes 1-2 parts by weight of a flame retardant, wherein the flame retardant includes 4-bromo-2-(2-bromoethyl)-1-methoxybenzene (CAS No.: 163260-76-2) and 4-bromo-3-chloro-2-fluorotoluene (CAS No.: 909122-30-1). In some embodiments, the mass fraction of the flame retardant is 1 part or 2 parts. If the mass fraction of the flame retardant is small, such as less than 1 part, the antistatic performance of the shape memory prestressed anchor mesh material is insufficient, and there is a safety hazard. If the mass fraction of the flame retardant is large, such as greater than 2 parts, it will have a negative impact on the mechanical properties and shape memory properties of the shape memory prestressed anchor mesh material.

[0038] According to an embodiment of the second aspect of the present application, a shape memory prestressed anchor mesh material is provided, which is prepared by the method described in any of the above embodiments.

[0039] According to an embodiment of the third aspect of the present application, it is proposed that the anchor mesh material in any of the above embodiments is used in shape memory prestressed support of a broken tunnel.

[0040] To facilitate further understanding of the present application, the scheme of the present application is further described below in conjunction with the embodiments. Those skilled in the art will understand that the description in the present application is only part of the examples, and any other suitable specific examples are within the scope of the present application.

[0041] Example 1

[0042] The present embodiment provides a shape memory prestressed anchor mesh material, and its preparation method and specific operating parameters are as follows: using (3-propyleneoxypropyl) tris(trimethylsiloxy)-silane, methacrylate-3(trimethoxysilyl)butyl ester and 3-(trimethylsiloxy)propylene in a mass ratio of 4:1:1 to jointly treat nano-concave attapulgite; forming active sites of carbon-carbon double bonds on the surface of the nano-concave attapulgite to obtain modified nano-concave attapulgite, adding the modified nano-concave attapulgite to a mixed active monomer composed of styrene, methyl methacrylate and butadiene, wherein the mass ratio of styrene, methyl methacrylate and butadiene is 2:1:5; then adding a composite catalyst composed of hexachloroplatinic (IV) acid and ferric nitrate in a mass ratio of 1:7, auxiliary heating to promote the polymerization reaction of carbon-carbon double bonds, introducing protective gas, such as nitrogen, etc., reacting at 300°C in a microwave reaction tube for 120 minutes, and preparing a modified styrene-methyl acrylate-butadiene copolymer with concave attapulgite as a chemical crosslinking point.

[0043] In parts by mass, 100 parts of modified styrene-methyl acrylate-butadiene copolymer, 6 parts of shape memory accelerator, 8 parts of shape memory critical temperature regulator, 1 part of anti-aging agent, 7 parts of reinforcing agent, 2 parts of plasticizer, 1 part of antistatic agent and 2 parts of flame retardant are stirred and mixed and melted at 130° C. The melt is spun and woven to obtain an anchor mesh material.

[0044] Example 2

[0045] This embodiment is different from Embodiment 1 in the following ways: in parts by mass, 110 parts of modified styrene-methyl acrylate-butadiene copolymer, 3 parts of shape memory promoter, 1 part of shape memory critical temperature regulator, 1 part of anti-aging agent, 5 parts of reinforcing agent, 1 part of plasticizer, 1 part of antistatic agent and 1 part of flame retardant are stirred and mixed and melted at 150°C, and the melt is spun and woven to obtain an anchor net material.

[0046] Example 3

[0047] This embodiment is different from Embodiment 1 in the following aspects: in parts by mass, 105 parts of modified styrene-methyl acrylate-butadiene copolymer, 7 parts of shape memory promoter, 2 parts of shape memory critical temperature regulator, 2 parts of anti-aging agent, 6 parts of reinforcing agent, 2 parts of plasticizer, 1 part of antistatic agent and 2 parts of flame retardant are stirred and mixed and melted at 140°C, and the melt is spun and woven to obtain an anchor net material.

[0048] Example 4

[0049] This embodiment is different from Embodiment 1 in the following ways: in parts by mass, 108 parts of modified styrene-methyl acrylate-butadiene copolymer, 3 parts of shape memory promoter, 4 parts of shape memory critical temperature regulator, 1 part of anti-aging agent, 7 parts of reinforcing agent, 1 part of plasticizer, 1 part of antistatic agent and 1 part of flame retardant are stirred and mixed and melted at 150°C, and the melt is spun and woven to obtain an anchor net material.

[0050] Example 5

[0051] This embodiment is different from Embodiment 1 in the following ways: in parts by mass, 102 parts of modified styrene-methyl acrylate-butadiene copolymer, 7 parts of shape memory promoter, 7 parts of shape memory critical temperature regulator, 2 parts of anti-aging agent, 7 parts of reinforcing agent, 3 parts of plasticizer, 1 part of antistatic agent and 2 parts of flame retardant are stirred and mixed and melted at 120°C, and the melt is spun and woven to obtain an anchor net material.

[0052] Experimental example

[0053] The anchor mesh materials in each embodiment were woven into a mesh and then tested. The results are shown in Table 1.

[0054] Table 1 Performance results of anchor mesh materials in the embodiment

[0055]

[0056] It can be seen from the results in Table 1 that the anchor net material provided by the present application has good support strength and high shape memory recovery rate, and can improve the support effect of the anchor net compared with the related technology.

[0057] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0058] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a shape memory prestressed anchor mesh material, characterized in that: The following steps are involved: Treating the nano-attapulgite to form active sites of carbon-carbon double bonds on its surface; The modified nano-attapulgite is added to the mixed active monomer, and reacted at 250-300° C. for 120-130 min under the action of a composite catalyst and a protective atmosphere to obtain a modified styrene-methyl acrylate-butadiene copolymer with the attapulgite as a chemical crosslinking point; In parts by mass, 100-110 parts of the modified styrene-methyl acrylate-butadiene copolymer, 3-7 parts of a shape memory accelerator, 1-8 parts of a shape memory critical temperature regulator, 1-2 parts of an anti-aging agent, 5-7 parts of a reinforcing agent, 1-3 parts of a plasticizer, 1 part of an antistatic agent and 1-2 parts of a flame retardant are stirred and mixed and melted at 100-150° C. The melt is spun and woven to obtain an anchor net material.

2. The preparation method according to claim 1, characterized in that: The method for treating the nano-concave convex rod to form active sites of carbon-carbon double bonds on its surface is: the nano-concave convex rod is treated with (3-propyleneoxypropyl) tris(trimethylsiloxy)-silane, methacrylate-3(trimethoxysilyl)butyl ester and 3-(trimethylsiloxy)propylene in a mass ratio of 4:1:

1.

3. The preparation method according to claim 1, characterized in that: The mixed active monomers include styrene, methyl methacrylate and butadiene in a mass ratio of 2:1:

5.

4. The preparation method according to claim 1, characterized in that: The composite catalyst comprises hexachloroplatinic (IV) acid and ferric nitrate in a mass ratio of 1:

7.

5. The preparation method according to claim 1, characterized in that: The shape memory promoter comprises vinyl polysilsesquioxane and amino polysilsesquioxane in a mass ratio of 5:

1.

6. The preparation method according to claim 1, characterized in that: The shape memory critical temperature regulator comprises polylactic acid, polycaprolactone and polyglycolide in a mass ratio of 1:1:

3.

7. The preparation method according to claim 1, characterized in that: The anti-aging agent comprises 5-bromoindole-2-carboxylic acid ethyl ester and 4-bromo-2-trifluoromethylquinoline in a mass ratio of 1:

2.

8. The preparation method according to claim 1, characterized in that: The reinforcing agent comprises pentaerythritol glycidyl ether, ethylene glycol diglycidyl ether and bisphenol A diglycidyl ether in a mass ratio of 4:1:

1.

9. A shape memory prestressed anchor mesh material, characterized in that: The method is obtained by any one of claims 1 to 8.

10. The anchor mesh material of claim 9 is used in shape memory prestressed support of broken tunnels.

Citation Information

Patent Citations

  • PVC foaming trough plate for suspended ceiling

    CN109354798A

  • Molecular orientation self-reinforced glass fiber reinforced plastic anchor rod and preparation method and application thereof

    CN117777672A

  • Anchoring-agent-free self-fastening glass fiber reinforced plastic anchor rod with shape memory performance and preparation method and application thereof

    CN118325293A

  • Methods and devices for collecting and classifying information on learning materials websites

    KR1020250020872A

  • High temperature shape memory polymers

    US20150284498A1